Foramen mentale’nin morfometrik özellikleri ve lokalizasyonunun üçüncü büyük azı dişleri ile ilişkisinin araştırılması - Yarkan, İlda Sinem (My University, 2025)
Amaç: Foramen mentale; mandibula ön kısmında bulunan, premolar dişlerin kökleri ile yakın ilişkide bir anatomik yapıdır. Foramen mentale’nin konumu bağıl olarak dişlerin çenedeki pozisyonlarına göre tanımlanmaktadır. Ancak dişler biyolojik süreçlere bağlı olan dinamik yapılardır. Söz konusu biyolojik süreçlerin öğelerinden en önemlilerinden biri de 3. molar dişleridir. Bu çalışmanın amacı foramen mentale’nin konumlandırılmasının 3. molar dişin sürme durumuna göre belirlenmesi ve aralarındaki olası ilişki üzerinden lokasyonunun radyolojik olarak araştırılmasıdır. Radyografik analizlerde incelenen üç ana faktör bulunmaktadır: foramen mentale’nin vertikal ve horizontal konumu, gonial açıları ve üçüncü molar dişin sürme durumu. Bulgular: Verilerin analizleri, üçüncü molar dişin tam sürmesi ile foramen mentale’nin vertikal ve horizontal konumu arasında istatistiksel olarak anlamlı bir ilişki olduğunu ortaya koymaktadır. Ayrıca bulgular, gonial açı ile üçüncü molar dişin sürme durumu arasında ise istatistiksel olarak anlamlı bir ilişki olmadığını göstermektedir. Sonuç: Bu çalışma üçüncü molar dişi varlığının/ yokluğunun foramen mentale’nin lokasyonunu doğrudan etkilediğini ortaya koymaktadır. Buna ek olarak üçüncü molar dişi oklüzyona yaklaştıkça foramen mentale distale ve inferior yöne doğru yer değiştirmekte olduğu da gösterilmiştir. Ayrıca bu çalışma, bu tür karmaşık ilişkileri yöneten temel mekanizmaları ayrıntılı bir şekilde araştırmayı amaçlayan gelecekteki araştırmalara da zemin hazırlamaktadır.

Purpose: The foramen mentale, an anatomical structure located in the anterior part of the mandible, is in close proximity to the roots of the premolar teeth. Its position is typically described relative to the placement of teeth in the jaw. However, teeth are dynamic structures influenced by biological processes. Among these processes, the eruption of the third molars plays a significant role. This study aims to determine the positioning of the foramen mentale in relation to the eruption status of the third molar teeth and to radiologically investigate its location based on their potential relationship. Materials and Methods: In this study, 254 panoramic radiographs of healthy individuals aged 18-45, obtained from the Kızıltoprak Imaging Center, were used. All radiographs were taken with a MORITA Veraview IC5 HD panoramic X-ray device. Measurements were performed using the open-source platform application Photopea. The collected data were analyzed using various statistical methods. Three main factors were examined in the radiographic analyses: the vertical and horizontal position of the foramen mentale, gonial angles, and the eruption status of the third molar. Results: Statistical analyses of the data reveal a relationship between the full eruption of the third molar and the vertical and horizontal position of the foramen mentale. Additionally, the findings show no statistically significant relationship between the gonial angle and the eruption status of the third molar. Conclusion: This study demonstrates that the presence/ absence of the third molar directly affects the location of the mental foramen. In addition, it has been shown that the mental foramen is displaced distally and inferiorly as the third molar approaches occlusion. This study also paves the way for future studies that aim to investigate in detail the basic mechanisms governing such complex relationships
Research of relationship between morphometric properties and localization of foramen mentale with third molars
Keywords: 3. büyük azı; Anatomi; Anatomy; Foramen mentale; mandible; mandibula; panaromic radiograph; panaromik grafi Mental foramen; third molar